Recent Synthetic Applications of the Birch Reduction - Linker, Torsten (Synlett, 2024)
The Birch reduction has found a renaissance during the last two decades. In this Synpacts article a short summary of selected recent synthetic applications will be provided. 1,4-Cyclohexadienes, which are formed by Birch reduction in one step, are suitable precursors for radical reactions and are used as surrogates for difficult-to-handle substances. Their rearomatization under acidic conditions offers easy access to selectively alkylated arenes. Additionally, the Birch reduction of benzoic acids and subsequent trapping afford spiro compounds in high yields. Very recently, it was shown that 1,3-cyclohexadienes are directly available by Birch reduction in a one-pot reaction as well.1 Introduction2 Rearomatizations3 Synthesis of Spiro Compounds4 Synthesis of 1,3-Cyclohexadienes5 Conclusion
Keywords: arenes; Birch reduction; cyclohexadienes; radical reaction; spiro compounds; synthetic applications